Determining adsorbate configuration on alumina surfaces with 13C nuclear magnetic resonance relaxation time analysis. Issue 32 (27th July 2015) - Vecino, P. A.; Huang, Z.; Mitchell, J.; McGregor, J.; Daly, H.; Hardacre, C.; Thomson, J. M.; Gladden, L. F.
Abstract : Relative strengths of surface interaction for individual carbon atoms in acyclic and cyclic hydrocarbons adsorbed on alumina surfaces are determined using chemically resolved 13 C nuclear magnetic resonance (NMR) T 1 relaxation times. Abstract : Relative strengths of surface interaction for individual carbon atoms in acyclic and cyclic hydrocarbons adsorbed on alumina surfaces are determined using chemically resolved 13 C nuclear magnetic resonance (NMR) T 1 relaxation times. The ratio of relaxation times for the adsorbed atoms T 1, ads to the bulk liquid relaxation time T 1, bulk provides an indication of the mobility of the atom. Hence a low T 1, ads / T 1, bulk ratio indicates a stronger surface interaction. The carbon atoms associated with unsaturated bonds in the molecules are seen to exhibit a larger reduction in T 1 on adsorption relative to the aliphatic carbons, consistent with adsorption occurring through the carbon–carbon multiple bonds. The relaxation data are interpreted in terms of proximity of individual carbon atoms to the alumina surface and adsorption conformations are inferred. Furthermore, variations of interaction strength and molecular configuration have been explored as a function of adsorbate coverage, temperature, surface pre-treatment, and in the presence of co-adsorbates. This relaxation time analysis is appropriate for studying the behaviour of hydrocarbons adsorbed on a wide range of catalyst support and supported-metal catalyst surfaces, and offers the potential to explore such systems under realistic operating conditions when multiple chemical components are present at the surface.